(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: Andragogy, the art and science of teaching adults, has emerged as a crucial framework for optimizing instructional methods and learning experiences for adult students. This article explores the key principles of andragogy and examines how educators can apply these principles to create vibrant, learner-centered classrooms that empower adult learners. By recognizing the unique needs, motivations, and characteristics of adult students, instructors can foster meaningful, relevant, and self-directed learning experiences that lead to transformative growth and development.